Anabolic-androgenic steroid users receiving health-related information; health problems, motivations to quit and treatment desires - Ingrid Amalia Havnes; Marie Lindvik Jørstad; Christine Wisløff (BMC, 2019)
Abstract Background Anabolic-androgenic steroids (AAS) are used to increase muscle strength and improve appearance, but users also carry the risk of developing physical and mental health problems. In Norway, the substance use disorder treatment system provides health care to this patient group, but few AAS users have sought such treatment. Therefore, a service was created to inform AAS users and next of kin of potential negative consequences and their treatment options. This study describes health problems, motivations for AAS cessation, and treatment desires among AAS users. Methods Over four years, 232 AAS users and 60 next of kin contacted the information service and received an hour-long information session with healthcare personnel. Information about AAS use, physical and mental health problems, substance use, motivation for cessation, and whether the information seeker desired treatment were registered. Qualitative interviews were conducted among seven individuals and analyzed thematically to explore information service experiences. Results Of the 232 AAS users, 179 (77.2%) desired treatment after completing the information session and 53 (22.9%) were unsure or did not want treatment. Those who desired treatment were significantly older, had used AAS longer, reported more physical and mental health side effects, and a higher proportion reported having children than those who did not desire treatment. Although 181 (78.0%) reported co-occuring physical and mental health problems, mental health problems were the most common motivation for AAS cessation (n = 108, 47.8%), followed by a combination of mental and physical health problems (52, 23.0%). Findings from qualitative interviews suggest that barriers to treatment may be overcome with an easily accessible service that informs about addiction treatment and facilitates the treatment entry process. Conclusions Healthcare professionals who encounter users of AAS should have knowledge about AAS use and adverse effects. The desire for health care reveals extensive health problems and the user group is so non-homogeneous that examination and treatment must be adapted individually with focus on physical, mental and social factors as well as possible dependence of AAS and/or psychoactive substances.